Time Domain Integration in Range Doppler/Angle Images for Human Gesture Recognition with FMCW Radar - Maiwald, Timo; Schmidt, Philipp; Fischer, Georg; Lurz, Fabian (Asia-Pacific Microwave Conference (APMC), 2025)
This paper presents a radar data labeling method and discusses results obtained by training a CNN for human gesture recognition with FMCW radar. Superimposed range-Doppler and range-angle images are used to integrate time dependent information into single images, which reduces the amount of data the CNN has to deal with. Obtained results indicate 92% accuracy in terms of the automated label assignment. An average classification accuracy of 85% is achieved, whereas this value drops by 2% only if in addition the CNN also differentiates between the left and right hand resulting in 23 categorie
Keywords: radar; fmcw; human gesture recognition; machine learning